The use of bromopyridazinedione derivatives in chemical biology. Issue 30 (4th April 2022) - Bahou, Calise; Chudasama, Vijay
Abstract : Herein we disclose the chemically unique features of the pyridazinedione scaffold and how these have been applied in various bioconjugation methodologies. Abstract : Tools that facilitate the chemical modification of peptides and proteins are gaining an increasing amount of interest across many avenues of chemical biology as they enable a plethora of therapeutic, imaging and diagnostic applications. Cysteine residues and disulfide bonds have been highlighted as appealing targets for modification due to the highly homogenous nature of the products that can be formed through their site-selective modification. Amongst the reagents available for the site-selective modification of cysteine(s)/disulfide(s), pyridazinediones (PDs) have played a particularly important and enabling role. In this review, we outline the unique chemical features that make PDs especially well-suited to cysteine/disulfide modification on a wide variety of proteins and peptides, as well as provide context as to the problems solved (and applications enabled) by this technology.